Morphological and cytochemical changes in synganglion of Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) female ticks from exposure of andiroba oil (Carapa guianensis) - Roma, Gislaine Cristina [UNESP]; Mathias, Maria Izabel Camargo [UNESP]; Faria, Adriano Uemura de [UNESP]; Oliveira, Patrícia Rosa de [UNESP]; Furquim, Karim Christina Scopinho [UNESP]; Bechara, Gervásio Henrique [UNESP] (Wiley, 2013)
Actually, the most used method to control ticks is synthetic acaricides with neurotoxic action. However, the use of these methods presents inconveniences, such as the contamination of the environment and risks to the host's health due to the residual effects. Thus, several studies have been developed aiming to find alternative ways to control these ectoparasites, such as the use of natural compounds with active ingredients, which act controlling some species of plagues in addition to presenting medicinal properties that are beneficial to humans. The present study aimed to analyze the action of andiroba oil (Carapa guianensis) on the synganglion of Rhipicephalus sanguineus semiengorged females through morphological and cytochemical techniques aiming to verify if this natural product have neurotoxic action as the numerous synthetic acaricides. The results showed that andiroba oil interferes in the synganglion through structural and enzymatic changes, which lead the nervous tissue to apoptotic death involving autophagy. Among these changes was observed the emergence of large empty spaces between the perineurium and the cortical region, vacuolated cortex cells and with cell swelling, neural cells with picnotic nuclei or in initial stage of chromatin margination and neuropile with high structural disorganization. Considering these data, it can be concluded that andiroba seed oil can be used as an alternative method in the control of R. sanguineus ticks due to its neurotoxic action. © 2013 Wiley Periodicals, Inc.
Keywords: Cell death; Central nervous system; Cytotoxicity; Natural product; Ticks; Acari; Carapa guianensis; Ixodida; Ixodidae; Rhipicephalus sanguineus